Associations of \(OTUBAIN-1, STAT, SHP\) and \(NF-KB2\) expression with clinical features in Non-Hodgkin’s lymphoma patients - Do Thi, Trang; Nguyen Trong, Ha; Nguyen, Xuan Thi (Academia Journal of Biology, 2024)
Non-Hodgkin’s lymphoma (NHL) is a group of lymphoproliferative disorders characterized by the abnormal proliferation and accumulation of lymphocytes in the lymphatic system. An ovarian tumor domain containing ubiquitin aldehyde binding protein 1 (Otubain-1) is a deubiquitinating enzyme that cleaves ubiquitin or ubiquitin-like molecules and is expressed in various human tissues. The pathogenesis of NHL is associated with activations of the nuclear transcription factor (NF-κB) and signal transducer and activator of transcription proteins (JAK/STAT) signaling pathways. In this study, all the expressions of Otubain-1, NF-κB2, SHPs and STATs genes, the concentrations of cytokines IL-1β, IL-6 and TNF-α and clinical features in NHL patients were examined. To the end, gene expression levels of 82 NHL patients and 56 healthy individuals were determined by quantitative real time RT-PCR and secretion of cytokines by ELISA. As a result, concentrations of IL-6 and TNF-α in the patient group were found higher than in the healthy individuals and patients with higher LDH concentrations in the clinical cutoff, 280 U/L showed increased concentrations of AST, ALT and GGT than those with normal LDH concentrations. Interestingly, NHL patients with high Otubain-1 expression had significant elevations of GGT and ferritin concentrations as well as STAT-5 expression compared to those with low Otubain-1 expression. In conclusion, the present study indicates that up-regulation of Otubain-1 led to activation of STAT5 in lymphoma cells and liver dysfunction and metabolic syndrome in NHL patients.